Sikap Mahasiswa Sastra Indonesia dalam Perkuliahan Daring pada Masa Pandemi Covid-19: Tinjauan Sistem Appraisal - Muh. Muchtasim; Mahmudah Mahmudah; Nensilianti Nensilianti (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. This qualitative research with descriptive explanation aims to describe the forms of attitude in the speech spoken by Indonesian Literature students class 2020 in attending online lectures during the COVID-19 pandemic and the factors that cause the problems of online lectures. The results of this study indicate that first, the attitudes in speech expressed by Indonesian Literature students class 2020 who attend online lectures are dominated by negative affect, Judgment aspect in this research is dominated by personal judgment rather than moral, and the factors that cause online lectures are divided into internal and external factors. Keywords: Attitude, online lectures, internal and external factors